Comparing an on-site nurse practitioner with telemedicine physician support hospitalist programme with a traditional physician hospitalist programme. (May 2019) - Boltz, Michelle; Cuellar, Norma G; Cole, Casey; Pistorese, Brent
Introduction: Since 2010, more than 75 rural hospitals have closed in the USA and more than one-third are at risk of closure due to lower patient volumes, lower funding levels, decreased hospital revenue and lower physician employment pools. Telemedicine can provide new models of care delivery that maintain quality and reduce cost of healthcare in rural populations. The purpose of this project was to evaluate a cross-organizational pilot program by comparing a NP/telemedicine physician hospitalist programme with a traditional physician hospitalist model to assess effects on length of patient stay, mortality rates, readmission rate, Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) ratings of provider communication, and total hospital costs. Methods: The Standard for Quality Improvement Reporting Excellence (SQUIRE) guidelines were followed. Using a one-year retrospective chart review, average length of stay, mortality rates, 30-day readmission rates and provider communication ratings were compared between hospitalists that were nurse practitioners working with physicians through telemedicine support and physicians alone. Results: There was no statistically significant variance in average length of stay, mortality rates, 30-day readmission rates, or provider communication ratings on HCAHPS surveys compared to the NP or physician hospitalist. Discussion: This new model of care demonstrates that telemedicine can be used to provide safe and efficient physician support from a regional hub medical centre to nurse practitioners practising as hospitalists in rural Critical Access Hospitals at up to 58% cost savings while maintaining quality of care and increasing access to community-based physicians.